Unsafe abortion and associated factors among reproductive aged women in Sub-Saharan Africa: a protocol for a systematic review and meta-analysis - Gebremedhin, M.; Semahegn, A.; Usmael, T.; Tesfaye, G. (Systematic Reviews, 2018)
Background Unsafe abortion is a neglected public health problem contributing for 13% of maternal death worldwide. In Africa, 99% of abortions are unsafe resulting in one maternal death per 150 cases. The prevalence of unsafe abortion is associated with restricted abortion law, poor quality of health service, and low community awareness. Hence, the aim of this systematic review and meta-analysis is to identify and summarize the available evidence to generate an abridged evidence on the prevalence of unsafe abortion and its associated factors in Sub-Saharan Africa. Methods The development of the systematic review methodology has followed the procedural guideline depicted in the preferred reporting items for systematic review and meta-analysis protocol statement. Observational studies that have been conducted from January 1, 1994, up to December 31, 2017, in Sub-Saharan African countries will be included in the systematic review and meta-analysis. MEDLINE (via PubMed), EMBASE, CINAHL, and PopLine will be searched to retrieve available studies. Relevant studies will be retrieved using the search strings applied to different sources. The Joanna Briggs Institute quality assessment tool will be used to critically appraise the methodological robustness and validity of the finding to avoid erroneous data due to confounded or biased statistics. Data extraction template will be prepared to record abstracted information from selected studies. The selection of relevant studies, data extraction, and quality assessment of studies will be carried out by two authors. Meta-analysis using Mantel–Haenszel random effects model will be carried out. The presence of heterogeneity between studies will be checked using the I2 value. Discussion Unsafe abortion is not yet reduced significantly in Sub-Saharan Africa, and maternal death rate due to unsafe abortion remains high. Currently, there is a gap in availability of abridged evidence on unsafe abortion and this negatively influenced the current service delivery. This finding will help stakeholders to design appropriate strategy. The finding of this systematic review and meta-analysis will be helpful to inform policy-makers, programmers, planners, clinician’s decision making, researchers, and women clients at large.
Keywords: Systematic review and meta-analysis; Unsafe abortion; Sub-Saharan Africa